Thin Nickel Coatings on Stainless Steel for Enhanced Oxygen Evolution and Reduced Iron Leaching in Alkaline Water Electrolysis - Deo, Yashwardhan; Thissen, Niklas; Seidl, Vera; Gallenberger, Julia; Hoffmann, Julia; Hofmann, Jan P.; Etzold, Bastian; Mechler, Anna K. (Electrochemical Science Advances, 2024)
One of the most mature technologies for green hydrogen production is alkaline water electrolysis. However, this process is kinetically limited by the sluggish oxygen evolution reaction (OER). Improving the OER kinetics requires electrocatalysts, which can offer superior catalytic activity and stability in alkaline environments. Stainless steel (SS) has been reported as a cost-effective and promising OER electrode due to its ability to form active Ni-Fe oxyhydroxides during OER. However, it is limited by a high Fe-to-Ni ratio, leading to severe Fe-leaching in alkaline environments. This affects not only the electrode activity and stability but can also be detrimental to the electrolyzer system. Therefore, we investigate the effect of different Ni-coatings on both pure Ni- and SS-supports on the OER activity, while monitoring the extent of Fe-leaching during continuous operation. We show that thin layers of Ni enable enhanced OER activities compared to thicker ones. Especially, a less than 1 µm thick Ni layer on an SS-support shows superior OER activity and stability with respect to the bare supports. X-ray photoelectron spectroscopy reveals traces of oxidized Fe species on the catalyst surface after OER, suggesting that Fe from the SS may be incorporated into the layer during operation, forming active Ni-Fe oxyhydroxides with a very low Fe leaching rate. Utilizing inductively coupled plasma-optical emission spectroscopy, we prove that thin Ni layers on SS decrease Fe leaching whereas the Fe from the uncoated SS-support dissolves into the electrolyte during operation. Thus, OER active and stable electrodes can be obtained while maintaining a low Fe concentration in the electrolyte. This is particularly relevant for application in high-performance electrolyzer systems.
CRIS-Team Scopus Importer:2025-02-04
Keywords: alkaline water electrolysis; electrodeposition; Fe leaching; oxygen evolution reaction; stainless steel